اتجاهات الطلبة الجامعيين الجزائريين نحو تغطية قناة الجزيرة الاخبارية للحرب على غزة بعد احداث السابع من اكتوبر 2023 - عائشة عيسات; الزهرة شقنان; د/ سليم بن معيزة (جامعة عمار ثليجي بالاغواط, 2025)
ملخص الدراسة هدفت هذه الدراسة إلى تحليل اتجاهات طلبة جامعة عمار ثليجي نحو تغطية قناة الجزيرة للحرب على غزة، ودراسة تأثير العوامل الديموغرافية على تشكيل هذه الاتجاهات. اعتمدت الدراسة على المنهج الوصفي التحليلي، وطُبقت على عينة من طلبة الجامعة بمختلف تخصصاتهم ومراحلهم الدراسية، مع التركيز على طلاب الإعلام والاتصال والعلوم الاجتماعية. كشفت الدراسة عن نتائج إيجابية استثنائية، حيث أظهر الطلبة اتجاهات إيجابية ساحقة نحو تغطية قناة الجزيرة بنسب تراوحت بين 77% و85% عبر مختلف مؤشرات التقييم. وقد شملت هذه النتائج الإيجابية جوانب المصداقية والشمولية والتوازن المهني والبعد الإنساني. أثبتت الدراسة نجاح قناة الجزيرة في تحقيق تأثير متعدد الأبعاد: • التأثير التعليمي: زيادة المعرفة بتفاصيل الصراع لدى 81% من المشاركين • التأثير الأكاديمي: استفادة 85% من الطلاب من التغطية كمادة بحثية • التأثير التعبوي: تعزيز قدرة 83% من المشاركين على مناقشة القضية • التأثير الإنساني: مساعدة 84% من المشاركين على التعاطف مع ضحايا الحرب أظهرت النتائج تحولاً جذرياً في عادات الاستهلاك الإعلامي نحو الوسائط الرقمية، حيث بلغت نسبة متابعة المنصات الرقمية 83%، مما يعكس نجاح استراتيجية قناة الجزيرة الرقمية. الكلمات المفتاحية: قناة الجزيرة ، تغطية إعلامية ، اتجاهات الطلبة Abstract This study aimed to analyze the attitudes of Omar Thalidji University students towards Al Jazeera's coverage of the war on Gaza and examine the impact of demographic factors on shaping these attitudes. The study employed a descriptive-analytical approach, applied to a sample of university students from various specializations and academic levels, with focus on media, communication, and social sciences students. The study revealed exceptional positive results, showing overwhelming positive attitudes among students towards Al Jazeera's coverage, with percentages ranging from 77% to 85% across different evaluation indicators. These positive results encompassed aspects of credibility, comprehensiveness, professional balance, and humanitarian dimension. The study demonstrated Al Jazeera's success in achieving multi-dimensional impact: • Educational Impact: Increased knowledge of conflict details amon80% of participants • Academic Impact: 85% of students benefited from coverage as research material • Mobilization Impact: Enhanced ability of 83% of participants to discuss the issue • Humanitarian Impact: Helped 84% of participants empathize with war victims Results showed a radical shift in media consumption habits towards digital platforms, with 83% following digital platforms, reflecting the success of Al Jazeera's digital strategy. Keywords: Al Jazeera Channel, Media Coverage, Student Trends
دراسة ميدانية على عينة من طلبة عمار ثليجي